Student Engagement with the Arabic Language on Social Media: A Media Exposure Approach to Language Learning - Shovi Maryam; Sutaman Sutaman; Miftahul Huda; Mufti Rasyid; Dissanayake, B. Y. (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2025)
This research aimed to determine the type and level of engagement with Arabic-language social media among students in the Arabic Language Education Department at Maulana Malik Ibrahim State Islamic University in Malang. The study employed a quantitative descriptive approach. The research population consisted of students from the Arabic Language Teaching Department, with a sample selected through purposive sampling, focusing on those who utilized social media for Arabic language learning in class. Data were collected using questionnaires featuring a Likert scale and brief interviews. The researchers employed descriptive statistical analysis to summarize and present the collected data in terms of frequencies, percentages, and means, providing an overview of students' participation in Arabic-language social networking platforms. The results of the research were as follows: (1) the students actively engage with social media for learning Arabic, their interaction is predominantly limited to grammar content created by Indonesian speakers, with minimal exposure to native Arabic media and cultural resources., and (2) the students occasionally engage with Arabic-language social media, mainly on Instagram and YouTube, but overall participation and consistency remain low. The limited and irregular exposure of students to Arabic-language media—particularly from native sources—suggests a missed opportunity in Arabic language pedagogy, where consistent engagement with authentic media could significantly enhance linguistic competence, cultural understanding, and communicative skills.